(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
The results of the study indicate the dependence of clinical, radiological and echographic signs of the articular syndrome in RA on environmental factors. Changes in the microelement composition of soil and air, depending on the area where RA patients live, contribute to the rate of progression of the articular syndrome.